Poverty, ethics and justice - Lötter, H. P. P. (Hennie P. P.) (Political philosophy now., 2011)
We understand poverty a lot better these days than even two decades ago. However, despite attempts by individuals, organizations, and governments, suffering caused by poverty persists on an alarming scale throughout the world. This book shows why it is so bad for humans to live in poverty. Poverty violates people's dignity and has lots of harmful consequences. The author presents ethical values to guide us to humanely and effectively help people trapped by poverty. The book gives reasons to motivate everyone to become involved in the struggle to eradicate poverty from the lives of people every.